Web-based student assembly information system in information technology program of muhammadiyah university, palembang - Aidil Fadli Tegriansyah; Meilyana Winda Perdana (Yayasan Pendidikan Rafisqy Arfadhia, 2023)
The rapid development of technology is also a reason why sophisticated technology is needed to help solve the problems experienced in an agency or organization. There are also organizations engaged in various fields student movement. They use internet technology as a place to promote their organization. As is the case with an organization called the Information Technology Student Association (HMTI) at Muhammadiyah University of Palembang. They use the Internet as a place to promote their organization, and to improve organizational performance. With the help of the internet, HMTI can be more flexible in reporting or informing the activities they do. In addition, they can also conduct consolidation and coordination via the internet. For example, if HMTI wants to hold an event that wants to invite various people to their event, HMTI not only informs their event through advertisements posted on the streets, they can also simply post the information via the internet whose scope is not only known. only by the people around him but not limited to any world.